In Vitro Experiments of Microwave Ablation in Liver Cancer Cells (Effects of Microwave Power and Heating Time) - Purachet Manop (2020)
© 2020 IEEE. Microwave ablation (MWA) is new promising alternative liver cancer treatment. It is a modality that use microwave energy to induce heat and then increase temperature within cancerous tissue to kill liver cancer cells. The cancer cell temperature of 50°C is required as starting point to induce cell death. Important parameters of MWA include microwave power, heating time as well as temperature achieved during the process. All of them affects effectiveness of this modality on killing cancer cells. In this research, in vitro experiment of MWA in liver cancer cells cultured (HepG2) is carried out. Cell viability of liver cancer cells then is measured using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay (MTT assay). Temperature distribution at various four points within cultured liver cancer cells is recorded during MWA. At the end of MWA, surface temperature profile of liver cancer cells is taken. Liver cancer cells undergo MWA based on microwave power of 5, 10 and 20 W for heating time of 10 min and microwave power of 20 W for heating time of 3, 5 and 10 min. Effects of microwave power and heating time on cell viability, temperature distribution as well as surface temperature profile of liver cancer cells are investigated. The results show that microwave power and heating time have the effect on cell viability significantly. Overall significant difference of cell viability is observed for each microwave power and heating time setting. Cell viability decreases with increasing microwave power and heating time. In addition, temperature distribution and surface temperature profile increase with increasing microwave power and heating time. Additionally, it is observed that temperature of liver cancer cells lasted for proper heating time is necessary to cause cell death. When the temperature reaches the target at 50°C for proper some time, MWA has efficiency in killing more than 50% of liver cancer cells. This research provides the essential aspects for planning cancer treatment using MWA in clinic.